Talking behind your back: Asymmetric communication in a three-person dilemma - Klaus Abbink; Lu Dong; Lingbo Huang (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2018)
Communication has been regarded as one of the most effective devices in promoting team cooperation. But asymmetric communication sometimes breeds collusion and is detrimental to team efficiency. Here, we present experimental evidence showing that excluding one member from team communication hurts team cooperation: the communicating partners collude in profit allocation against the excluded team member, and the latter reacts by refraining from exerting effort. We further show that allowing the partners to reach out to the excluded member helps to restore cooperation and fairness in profit allocation. But it does not stop the partners from talking behind the other member. They sometimes game the system by tricking the excluded member to contribute but then grabbing all profits for themselves.
Keywords: D62; H41; C79; C90; D63; 330; communication; fairness; collusion; allocation; team cooperation; laboratory experiment